PPENERAPAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KETERAMPILAN PROSES SISWA KELAS IV SEKOLAH DASAR BAWAMAI PONTIANAK - Yulianti, Eka; Rosnita, Rosnita; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this thesis is â€œWhether the application of contextual teaching and learning in natural science learning can improve the process skills of fourth grade students ofÂ  Bawamai Pontianak Elementary School ?â€. The purpose of general research is to describe the ability of teachers to design and implement learning science and describe the improvement of studentsÂ  process skills with the application ofÂ  contextual teaching and learning. The subject of this research is a teachers implementing the action and Class IV B as much as 36 students The design of this study uses a class action design. Data collection tool used in this research is observation, test and documentation in the form of photo and video during the research. The results obtained are the average score of teacher's ability to plan the learning natural science is very good that is an increase from 78 to 98. The ability of teachers in implementing science lessons with a very good category that is 62 to 84. That is, the application of contextual teaching and learning gave effect the process skills of fourth grade students of Bawamai Pontianak Elementary School.Â Keywords : Contextual Teaching and Learning, Â Process Skill, Science LearningÂ